2022
DOI: 10.3390/plants11020159
|View full text |Cite
|
Sign up to set email alerts
|

Root Morphology, Allometric Relations and Rhizosheath of Ancient and Modern Tetraploid Wheats (Triticum durum Desf.) in Response to Inoculation with Trichoderma harzianum T-22

Abstract: Early root traits and allometrics of wheat are important for competition and use of resources. They are under-utilized in research and un-explored in many ancient wheats. This is especially true for the rhizosheath emerging from root-soil interactions. We investigated root morphology, root/shoot relations and the amount of rhizosheath of four tetrapoid wheat seedlings (30 days after emergence): the italian landrace Saragolle Lucana and modern varieties Creso, Simeto and Ciclope, and tested the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
4
14
0
Order By: Relevance
“…The production of growth-stimulating hormones and secondary metabolites, and the modifications of the root architecture induced by T-22 through seed coating are also suggested by our results of the evident effects on the shoot height and main root length in all the varieties (Table 4). In particular, the effect on the shoot height in Saragolle Lucana and the main root length in Ciclope and Simeto confirmed the recent assessment reported by [19]. It was demonstrated that T. harzianum spp.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The production of growth-stimulating hormones and secondary metabolites, and the modifications of the root architecture induced by T-22 through seed coating are also suggested by our results of the evident effects on the shoot height and main root length in all the varieties (Table 4). In particular, the effect on the shoot height in Saragolle Lucana and the main root length in Ciclope and Simeto confirmed the recent assessment reported by [19]. It was demonstrated that T. harzianum spp.…”
Section: Discussionsupporting
confidence: 85%
“…On this basis, our previous results regarding seedling growth, with the best performance shown by Simeto, suggest that this variety can modify its root architecture by increasing the amount of rhizosheath more than other varieties when T-22 is provided as a seed coating [19]. Hence, this specific T. harzianum T-22 inoculation method resulted in root colonization that was characterized by a less dense coiling (see Figure 3) and by the possible production of root exudates and/or specific secondary metabolites that are able to alleviate the oxidative stress induced by F. culmorum [28] and affect T-22-Simeto-pathogen interaction.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations